(untitled) (Journal of actual problems of jurisprudence, 2018)
The article deals with the essence of eknomicheskoy security and issues related to the role of customs authorities in ensuring the economic security of the Republic of Kazakhstan. In fact, those disclosed link national and economic security, the main tasks and fnuktsiyami Customs Service Effectiveness aimed to ensure the functioning of the external economic relations and to protect them from the effects of external destructive forces. And also, an attempt is made to analyze the norms of law provides for the implementation of measures Priman state in this field. Key words: national security, economic security, social and economic system, foreign economic activity, customs activities, strategic direction, pravovohranitelnaya activity, fiscal policy, reform.